ACCESS AND DISTRIBUTION OF PRONAF BETWEEN FAMILY FARMERS IN THE STATE OF CANTA CATARINA (Desenvolvimento em Questão, 2020)
This article has as its theme the participation and access of family agriculture in the state of Santa Catarina in the National Program for Strengthening Family Agriculture (PRONAF)., The objective was to analyze the trajectory of access and distribution of PRONAF credit in the state of Santa Catarina. The study is characterized by an approach that involves both the use of quantitative and qualitative methods, having as its boundary the state of Santa Catarina and the registration of access to the PRONAF program between 1996 and 2018. The data resulting from the survey were accessed with the Central Bank, considering the resources deflated by the INPC for the year 2018. The results point to growth in the volume of resources distributed in the period from 1996 to 2018, accounting for approximately 6.2 times the initial value, equivalent to 619.1%. On the other hand, the number of contracts showed oscillations, from 98 thousand in 1996 to 90 thousand contracts in 2018, allowing to verify that the amount accessed by producer is greater. The largest portion of the credit resources is allocated to funding, which did not prevent the recording of significant increases from 2006 on the investment credit line. There is a concentration of financing in crops / activities linked to large agribusiness chains in the state. It is possible to conclude that PRONAF consists of an important public policy to support the rural family segment of the state of Santa Catarina, since it has increased the amount accessed, at the same time as it points to the selectivity of the program participants and growth in the need for financial resources.
Keywords: Rural credit; Public policy; Countryside.